Zinc-Mediated Diastereoselective Acyloxyallylation of Isoxazolidine-4,5-diols - Ďurina, Lukáš; Kerti, Lukáš; Litecká, Miroslava; Moncol, Ján; Žídeková, Ivana; Fischer, Róbert (Synthesis, 2025)
The synthesis of new N-Boc- and N-Cbz-protected δ-(hydroxyamino)-α,β,γ-triols is described for the first time. Products were prepared from 3,4-trans-isoxazolidine-4,5-diols, containing different substituents at the C-3 position, by a zinc-mediated acyloxyallylation reaction in good to excellent yields with excellent 3,4-anti simple diastereoselectivity and good 4,5-syn facial diastereoselectivity. Reductive cleavage of the N–O bond can provide δ-amino-α,β,γ-triol, thus demonstrating the potential synthetic utility of δ-(hydroxyamino)-α,β,γ-triols as useful building blocks for bioactive molecules.
Keywords: isoxazolidine-4,5-diols; acyloxyallylation; (hydroxyamino)triols; diastereoselectivity; crystal structures